Alfalfa supplementation timing changes the rumen archaeal and fungal community composition and colonization in pre-weaning lambs - Li, Kenan; Du, Haidong; Guo, Wenliang; Na, Meila; Na, Renhua (Frontiers in Microbiology, 2024)
The establishment of the rumen microbiota plays an important role in the rumen development. However, little is known about the effects of alfalfa supplementation time on rumen microbiota establishment. Here, a total of 42 Hu lambs, seven-day-old, were chosen for the study. After a week of adjustment, six lambs were sacrificed to establish a baseline. The remaining 36 lambs were randomly split into two groups: one receiving alfalfa hay at 14 days (EAF), the other at 42 days (LAF), both groups received milk replacer and starter pellets. Introducing alfalfa at 14 days of age significantly improved total dry matter intake between 28 and 42 days (P = 0.04) and average daily gain from both 14 to 28 days (P = 0.04) and 28 to 42 days (P < 0.01), but this effect disappears from 56 to 70 days (P > 0.05). At 42 days, the abundances of Naganishia, Ascochyta, and Neosetophoma in the EAF group were significantly higher (P < 0.05) than those in the LAF group (17.8% vs 3.97%, 10.89% vs 1.77%, and 1.27% vs 0.09%, respectively). At 56 days, the abundances of Ascochyta, Wallemia, and Aspergillus in the EAF group were significantly lower (P < 0.05) than in the LAF group (3.53% vs 16.40%, 8.78% vs 18.89%, and 2.14% vs 4.69%). At 70 days, Aspergillus abundance in the EAF group was significantly higher (P < 0.05) than in the LAF group (2.69% vs 0.85%). The LEfSe analysis showed that Methanobrevibacter_smithii was the archaeal biomarker at 14 days in both groups. Methanobrevibacter_sp_AbM4 was enriched at 56 days in the LAF group. Compared to the LAF group, the specific fungal biomarkers in the EAF group included Ascochyta, Neoascochyta, and Alfaria at 14 days, Naganishia, Didymella, Cleistothelebolus, and Alloleptosphaeria at 56 days, Sporobolomyces and Bullera at 70 days. Correlation analysis results showed strong patterns of association both within and between archaea and fungi, which were influenced by alfalfa supplementation time. In summary, alfalfa supplementation at 14 days of age promotes the growth performance of lambs before weaning, and alfalfa supplementation timing significantly affects rumen archaeal and fungal communities and dynamical changes.